Optimal wound closure of diabetic foot ulcers with early initiation of TLC-NOSF treatment: post-hoc analysis of Explorer. (2nd June 2019) - Lázaro-Martínez, José Luis; Edmonds, Michael; Rayman, Gerry; Apelqvist, Jan; Van Acker, Kristien; Hartemann, Agnès; Martini, Jacques; Lobmann, Ralf; Bohbot, Serge; Kerihuel, Jean-Charles; Piaggesi, Alberto
Abstract : Objective: In March 2018, the Explorer study, an international, double-blind, randomised controlled trial (RCT), established that adding a TLC-NOSF (UrgoStart Contact, Laboratoires Urgo, France) dressing to good local standard of care (SoC) significantly and substantially increases wound closure and reduces the healing time of neuroischaemic diabetic foot ulcers (DFU). Besides the TLC-NOSF treatment, the wound duration was the only other covariate that had an influence on the wound closure rate in the regression model used in the original study. The purpose of this work was to further document the impact of wound duration on the healing outcomes of the DFUs included in the Explorer study and to discuss complementary pragmatic observations on the TLC-NOSF effect. Method: In this post-hoc analysis of the Explorer data, the wound closure rates by week 20 are reported for the global cohort (n=240, Intention-to-treat population) and for the treated (n=126) and control groups (n=114) according to DFU duration and location. Results: For the combined group, wound closure rates decreased with the increase of wound duration at baseline (from 57% in wounds ≤2 months to 19% in wounds >11 months). Whatever the wound duration subgroups analysed, higher closure rates were reported in the TLC-NOSF group than in the control group. However, the maximal difference between the two treatments was reported in wounds with a duration of ≤2 months (71% versus 41%, 30 percentage points difference, Relative Risk 1.7, 95% Confidence Interval 1.1 to 2.8). Regarding wound location subgroup analyses, the outcomes were always in favour of the TLC-NOSF treatment, with closure rates ranging between 43% and 61% within the TLC-NOSF group, and between 25% and 40% within the control group. Conclusion: This clinical evidence supports that treating DFUs with TLC-NOSF dressing and good SoC results in higher wound closure rates than with a neutral dressing and the same good standard of care, whatever the duration and the location of the treated wounds. However, the earlier the TLC-NOSF dressing is initiated in DFU treatment, the greater the benefits.